2017
DOI: 10.1590/0100-29452017859
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY INDEX AND HARVEST MATURITY OF Eugenia cibrata FRUITS

Abstract: -the aim of this study was to characterize and determine the quality index and the harvest maturity of Eugenia cibrata fruits. Fruits were harvested at 39, 41 and 43 days after sprouting and selected by the larger size. Fruits ripened on the plant until complete abscissions were considered standard for determining the quality index after harvest. Samples were analyzed at harvest day and at two days of storage at temperature of 26 ± 2 ° C and relative humidity of 85-90%. The following items were evaluated: firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…sobralianum fruits presented longitudinal diameter (LD) of 27.593 ± 2.4685 mm, and transversal diameter (TD) of 26.493 ± 2.2212 mm (Figure 2), as in the classification of Landrum and Proença (2015). Diniz et al (2017) found similar diameters (LD of 32.8 mm ± 16.0, and TD of 33.6 mm ± 17.0) for Eugenia cribrata McVaugh. However, they were smaller than those found for Eugenia uniflora L. (width of 10-12 mm and length of 12-15 mm) (SMIDERLE; SOUZA; SOUZA, 2016), and Eugenia dysenterica DC.…”
Section: Morphological Characterizationmentioning
confidence: 67%
“…sobralianum fruits presented longitudinal diameter (LD) of 27.593 ± 2.4685 mm, and transversal diameter (TD) of 26.493 ± 2.2212 mm (Figure 2), as in the classification of Landrum and Proença (2015). Diniz et al (2017) found similar diameters (LD of 32.8 mm ± 16.0, and TD of 33.6 mm ± 17.0) for Eugenia cribrata McVaugh. However, they were smaller than those found for Eugenia uniflora L. (width of 10-12 mm and length of 12-15 mm) (SMIDERLE; SOUZA; SOUZA, 2016), and Eugenia dysenterica DC.…”
Section: Morphological Characterizationmentioning
confidence: 67%
“…The values of pulp yield described in other fruits of the same genus of the species were 68% for the perfume guava (Campomanesia lineatifolia) and 46% in the guavira (Campomanesia adamantium) (Pelloso, Vieira, & Zárate, 2008;Morzelle, Bachiega, Souza, Boas, & Lamounier, 2015). In other native species of the Myrtaceae family, the following values have been recorded: 72% for the camu-camu (Eugenia cibrata), 79% for the pitanga (Eugenia uniflora), 45% for the araçá-do-campo (Psidium guineense) and 75% for the araçápêra (Psidium acutangulum) (Diniz, Araújo-Neto, Novalli, Nogueira, & Silva, 2017;Batista, Fonseca, Carvalho, & Bittencourt, 2017). When comparing pulp yield data obtained in the present study with those of other referenced species, we may confirm that sete capotes is outstanding.…”
Section: Resultsmentioning
confidence: 99%